Cattle use of prairie dog towns on the Shortgrass Steppe of Colorado - Guenther, Debra A., author; Detling, James K., advisor; Rittenhouse, L. R. (Larry Ronald), 1940-, committee member; Steingraeber, David Allen, 1953-, committee member (Colorado State University. Libraries, 2000)
Studies on the mixed-grass prairie have found that native large herbivores preferentially graze on prairie dog towns. I investigated the use of prairie dog towns by cattle (Bos taurus) in northeast Colorado by conducting surveys of cattle and vegetation on the Shortgrass Steppe Long Term Ecological Research Site from June-August, 1999. Twelve pastures containing 15 black-tailed prairie dog (Cynomys ludovicianus) towns were surveyed three times a week, and the number of cattle on the towns and their behavior were recorded. A subset of three pastures was intensively surveyed twice weekly wherein the habitat and activity of a randomly chosen focal animal was recorded every six minutes for 3.5 hours. Bite and step counts of other individuals were recorded for five-minute intervals. Vegetation height and cover data were collected monthly on each of the six habitat types. Resource selection functions for driving survey data indicated no significant difference between prairie dog town use and availability. Regression analysis showed no correlation between rain events and prairie dog town use by cattle. The intensively surveyed pastures yielded similar results: i.e., cattle did not significantly prefer or avoid the prairie dog towns. Cattle spent 60% of their time grazing, 13% resting, and 15% traveling when present on prairie dog towns. These percentages were not significantly different from most other habitat types. There were no significant differences in the number of bites per step taken by cattle on towns compared to off town swales, Atriplex canescens terraces, and crested wheatgrass (Agropyron cristatum) strips. Five plant species palatable to cattle occurred in relatively high frequencies (36-65%) on prairie dog towns. In general, bare ground, litter, and vegetation cover on prairie dog towns did not significantly differ from most other habitat types. Vegetation on prairie dog towns was however significantly shorter on (mean= 6.7cm) than that off (mean= 11.9cm) prairie dog towns. This research indicates that cattle on the shortgrass steppe use prairie dog towns randomly and do not avoid them despite the shorter vegetation on prairie dog towns. However, cattle do not prefer to graze on prairie dog towns as bison (Bison bison) do on the mixed-grass prairie.
Keywords: Cattle -- Feeding and feeds -- Colorado; Grazing -- Colorado